Moringa oleifera Leaf Extract Ameliorates Photooxidative Damage and Photoaging Induced by Ultraviolet-B in HaCaT Keratinocytes - Tanaporn Hengpratom; Benjawan Dunkhunthod; Kittipot Sirichaiwetchakoon; Pimchaya Prompradit; Issara Chaisit; Mariena Ketudat-Cairns; Salila Pengthaisong; James R. Ketudat-Cairns; Yothin Teethaisong (Antioxidants)
Skin damage and premature aging are predominantly driven by UV radiation through several mechanisms. The most common of these are by reactive oxygen species (ROS) generation, upregulation of matrix metalloproteinases (MMPs), and weakened antioxidant defenses. Moringa oleifera is a nutritionally valuable plant with diverse biological activities. This study optimized ethanol concentrations coupled with ultrasonic-assisted extraction to maximize the yield and efficacy of M. oleifera leaf extract (MOLE). We also elucidated the underlying mechanisms of MOLE in protecting against photooxidative damage and skin aging from UVB exposure in HaCaT keratinocytes. Extraction with 50% ethanol produced the highest total phenolic and flavonoid contents, aligning with the greatest antioxidant activity by ABTS and FRAP assays. MOLE showed no significant cytotoxicity up to 1000 µg/mL in the MTT assay. MOLE protected cells from detrimental UVB radiation by scavenging ROS; reducing cell damage and death; enhancing gene expression of superoxide dismutase (SOD-1), glutathione peroxidase (GPx), and catalase (CAT); and improving SOD activity. UVB exposure elevated MMP-1, MMP-3, and MMP-9 expression and decreased collagen type I (col-1) and elastin (ELN) expression, while these effects were ameliorated by MOLE. Our findings suggest that MOLE protected against UVB-induced photooxidative damage and premature aging in the HaCaT keratinocytes.